Regionalism Versus Multilateralism - Thomas, Christopher R. author. aut Link
XI, 173 p.
Keywords: In today's globalized international system, international and regional organizations can only function effectively within the context of a larger social partnership with governments, the private sectors, and a plethora of increasingly influential interest groups. Regionalism Versus Multilateralism seeks to illustrate these new roles by tracing the way the Organization of American States (OAS), the oldest regional organization, has pursued its objectives in the context of evolving hemispheric and international circumstances. It analyzes the impact of these circumstances on the operations, programs and activities of the Organization, and the adjustments and direction which `metamorphosed' the regional membership at certain crucial junctures of hemispheric and international evolution. The book does so in three parts: through an historic examination of the objectives of the Organization; a critical analysis of its response over time to the forces of growth, transformation and change; and the projection of what continuing developments might dictate on the future characteristics of the Organization if it is to respond effectively to the needs and aspirations of member states. This book is a collaboration between Christopher R. Thomas and Julian T. Magloire, with both parties contributing equally to its content and preparation.